1983
DOI: 10.1159/000182901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peritoneal Dialysis on Plasma Levels of Ascorbic Acid

Abstract: The effect of peritoneal dialysis on plasma ascorbate levels was investigated in 32 patients suffering from end-stage renal disease. Our studies demonstrated a high peritoneal clearance of ascorbic acid resulting in a significant loss into the dialysate. The quantity of ascorbic acid lost by patients undergoing peritoneal dialysis was proportional to the predialysis ascorbic acid levels. Since the ascorbic acid lost from the plasma during peritoneal dialysis is not adequately replaced by dietary consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The values of the mean peritoneal clearances of vitamin C and oxalic acid were comparable with data in the literature ( 1, 3, 6, 7, 16, 23).…”
Section: Discussionsupporting
confidence: 87%
“…The values of the mean peritoneal clearances of vitamin C and oxalic acid were comparable with data in the literature ( 1, 3, 6, 7, 16, 23).…”
Section: Discussionsupporting
confidence: 87%
“…Vitamin C intake is comparable among the nondialyzed and CPD patients and healthy subjects. In ESRD patients, plasma ascorbate level is, therefore, reduced in part due to uremia-associated metabolic derangement and further decreased owing to peritoneal loss of ascorbic acid during PD (8,9). Information on plasma vitamin E in CPD patients is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators showed that PD is accompanied by significant loss of the antioxidant ascorbic acid and therefore, supplementation of this vitamin could be beneficial [ 105 ]. Shah et al reported that oral intake of ascorbic acid resulted in a 45% increase of serum ascorbic acid levels in chronic PD patients [ 106 ].…”
Section: Antioxidant Administration In Pdmentioning
confidence: 99%